Hubungan antara pengetahuan tentang HIV/AIDS dengan pemeriksaan voluntary counseling and testing (VCT) pada ibu hamil - Laiya, Nining; Asrifuddin, Afnal; Nelwan , Jeini Ester (Holistik Jurnal Kesehatan, 2026)
Background: Voluntary counseling and testing (VCT) is a confidential, voluntary process of pre-testing and post-testing for HIV/AIDS that helps individuals learn their HIV status early, which is crucial for prevention and treatment. VCT is crucial for pregnant women because it aims to prevent mother-to-child transmission of HIV, and to prevent and manage HIV-related illnesses. Purpose: To examine the relationship between knowledge about HIV/AIDS and voluntary counseling and testing (VCT). Method: This was a quantitative cross-sectional study. The sampling technique used purposive sampling, with 72 pregnant women as the sample. Data analysis used Fisher's exact test. Results: 55 participants (76.4%) had good knowledge and 17 participants (23.6%) had poor knowledge. 62 participants (86.1%) had received VCT, while 10 (13.9%) had not. Conclusion: There is a significant relationship between knowledge about HIV/AIDS and voluntary counseling and testing (VCT) with p-value = 0.020.   Keywords: Knowledge about HIV/AIDS; Pregnant Women; Voluntary Counseling and Testing (VCT).   Pendahuluan: Voluntary counseling and testing (VCT) adalah proses konseling pre testing, konseling post testing HIV/AIDS secara sukarela yang bersifat rahasia dan secara lebih dini membantu orang mengetahui status HIV yang penting untuk pencegahan dan perawatannya. VCT penting bagi ibu hamil karena bertujuan pencegahan penularan HIV dari ibu ke anak, pencegahan dan manajemen klinis penyakit-penyakit yang berhubungan dengan HIV. Tujuan: Untuk melihat hubungan antara pengetahuan tentang HIV/AIDS dengan pemeriksaan voluntary counseling and testing (VCT). Metode: Penelitian kuantitatif dengan pendekatan cross-sectional. Teknik pengambilan sampel pada penelitian ini menggunakan purposive sampling, yang terdiri 72 ibu hamil sebagai sampel. Analisis data menggunakan fisher’s exact test. Hasil: Pengetahuan tentang HIV/AIDS yaitu sebanyak 55 responden (76.4%) yang berpengetahuan baik dan sebanyak 17 responden (23.6%) yang berpengetahuan buruk. Responden sebanyak 62 (86.1%) sudah melakukan pemeriksaan VCT dan sebanyak 10 (13.9%) tidak melakukan pemeriksaan VCT. Simpulan: Terdapat hubungan signifikan antara pengetahuan tentang HIV/AIDS dengan pemeriksaan voluntary counseling and testing (VCT) dengan p-value= 0.020.   Kata Kunci: Ibu Hamil; Pengetahuan HIV/AIDS; Voluntary Counseling and Testing (VCT).